From Faults to Festivals: A Geotourism Strategy Based on Geological and Geophysical Analysis in Prambanan - Pangestu, Farizki Budi; Darmawangsa, Wahyu Ramadhan; Pintrandhita, Anwar Said; Lapian, Gianangel Emmanuela; Widagdo, Arif Surya (Advances in Tourism Studies, 2024)
This study explores the development of geotourism in the Prambanan region of Yogyakarta by integrating geological, geophysical, and cultural data to design a strategic geotrail. Located along the Opak Fault and rich in volcanic history, Prambanan features diverse geosites such as Tebing Breksi, Lava Bantal Berbah, and Candi Abang. Through a multidisciplinary methodology combining geological mapping, gravity surveys, and cultural site assessments, six key geosites were evaluated using Kubalikova’s framework. Tebing Breksi emerged as the most feasible site due to its rich pyroclastic breccia formations and cultural functions, while other sites showed moderate to high potential. Geophysical analysis using the Lacoste & Romberg gravitymeter revealed fault structures critical to infrastructure safety and disaster mitigation. The study proposes the development of integrated geotrails supported by educational panels, improved facilities, community involvement, and conservation strategies. By connecting geological significance with cultural heritage and local livelihoods, this research supports the sustainable enhancement of tourism infrastructure in Prambanan. The findings provide valuable input for policymakers, tourism planners, and educators, emphasizing the role of geoscience in destination development. Limitations include the need for deeper geotechnical and socio-economic impact studies. Future research may explore visitor engagement and smart tourism technologies for enriched geosite experiences.